2010
DOI: 10.5336/medsci.2008-10117
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Colon Tumorigenesis Induced by 1,2 Dimethylhydrazine in Balb/C Mice

Abstract: o lo rek tal kar si nom, ge liş miş ül ke ler de cid di mor bi di te ve mor ta li teye yol açan önem li bir kan ser tü rü dür. Gö rül me sık lı ğı di yet ile yakın dan iliş ki li olup bu has ta lı ğın gö rül me ora nı git tik çe Turkiye Klinikleri J Med Sci 2010;30(3) 1015 1,2-Dimetilhidrazin ile Balb/C Türü Farelerde Deneysel Kolon Kanserinin İndüklenmesi ÖZET Amaç: Ko lon kan se ri dün ya da sık lık la gö rü len kan ser tür le rin den bi ri dir. Ne op las tik has talık la rın de ney sel hay van mo del le ri,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…It has been reported that DMH induces mutations predominantly in the colon, as compared to the small intestine (Newell and Heddle, 2004). We have previously shown that s.c. injection of 20 mg/kg/week DMH during the 12 weeks caused 100% epithelial dysplasia at weeks 6 and 100% carcinoma at week 18 after the last injection of DMH (Karaca et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that DMH induces mutations predominantly in the colon, as compared to the small intestine (Newell and Heddle, 2004). We have previously shown that s.c. injection of 20 mg/kg/week DMH during the 12 weeks caused 100% epithelial dysplasia at weeks 6 and 100% carcinoma at week 18 after the last injection of DMH (Karaca et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Eighteen weeks after the last injection, all mice were killed with an overdose of ketamine. Our previous work showed that s.c. injection of DMH 20 mg/kg/week during the 12 weeks caused 100% carcinoma at week 18 after last injection (Karaca et al, 2010). After the death of the animal, the abdomen was opened and approximately 7–8-cm long large intestine was cut between cecum and anal canal by a scissors.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study, we found that subcutaneous injection of 20 mg/kg/week of DMH during the 12 weeks caused 100% epithelial dysplasia at the following 6th week and 85% high grade dysplasia at the following 12th week after last injection (Karaca et al, 2010). The phase, where 85% high grade dysplasia was seen, was a critical period in terms of precancerous conditions.…”
Section: Treatment Protocolmentioning
confidence: 91%
“…In our previous study using the DMH carcinogenic model, different durations of treatment free intervals were used. We found that subcutaneous injection of 20 mg/kg/week DMH during 12 weeks caused 100% epithelial dysplasia in the following 6th week (Karaca et al, 2010). The phase, at which 100% epithelial dysplasia was seen, was a critical period in terms of precancerous conditions.…”
Section: Methodsmentioning
confidence: 96%
“…It was then opened longitudinally using scissors, washed with phosphate-buffered saline and the mucosal surface examined for gross pathology (number and distribution of the neoplasms). Following macroscopic examination, the colon tissues were prepared for histopathologic examination according to the Swiss-roll technique (Karaca et al, 2010; Moolenbeek and Ruıtenberg, 1981; Reilly and Kirsner, 1965). This technique allows the entire intestinal mucosa to be examined efficiently.…”
Section: Methodsmentioning
confidence: 99%